2009
DOI: 10.1111/j.1751-2980.2009.00384.x
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA expression profile in non‐cancerous colonic tissue associated with lymph node metastasis of colon cancer

Abstract: OBJECTIVE:To identify microRNA expression patterns associated with the lymph node metastasis of colon cancer. METHODS:MicroRNA were isolated from six frozen non-cancerous surrounding colonic tissues derived from stage II-III colon cancer patients with (n = 3) and without (n = 3) lymph node metastasis. We compared the microRNA expression profiles of the six non-cancerous colonic tissues from two colon cancer patient groups; those with confirmed lymph node metastasis, termed the lymph node positive group, and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Epigenetic regulation of miR-129-2 was reported in glioma and lung cancer (8,9). In contrast, however, miR-129 is also upregulated in several solid tumors and non-cancerous tissues from cancer patients with lymph node metastases (29,30). Our results revealed the tumor-suppressor functions of miR-129-2.miRNAs degrade or repress translation of target mRNAs.…”
Section: Discussionmentioning
confidence: 59%
“…Epigenetic regulation of miR-129-2 was reported in glioma and lung cancer (8,9). In contrast, however, miR-129 is also upregulated in several solid tumors and non-cancerous tissues from cancer patients with lymph node metastases (29,30). Our results revealed the tumor-suppressor functions of miR-129-2.miRNAs degrade or repress translation of target mRNAs.…”
Section: Discussionmentioning
confidence: 59%
“…Given the unique feature of their targeting, each single miRNA may have over a hundred targets, and, thus, a large number of protein-coding genes may be regulated by miRNAs (21). Huang et al (22) performed a comparison of the miRNA profile of tumor-adjacent non-cancerous colonic samples in CRC with lymph node metastasis with those without lymph node metastasis. Their results indicated that hsa-miR-129* and hsa-miR-137 were significantly differentially expressed.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, chromosome 7q32 is a frequently deleted region in many cancers 20 21. MiR-129 family seem to behave as a tumour suppressor and their decreased expression has been shown in different tumours such as: gastric,22 bladder,23 and endometrial cancer,24 hepatocellular25 and colorectal carcinoma,26 lung adenocarcinoma27 and GBM 11. However, the precise role of miR-129-1 in GBM cancer pathology remains to be defined.…”
Section: Introductionmentioning
confidence: 99%